Epidural corticosteroid injections for sciatica: a randomised, double blind, controlled clinical trial. Issue 7 (1st July 2003) - Valat, J-P; Giraudeau, B; Rozenberg, S; Goupille, P; Bourgeois, P; Micheau-Beaugendre, V; Soubrier, M; Richard, S; Thomas, E
Abstract : Objective: To determine the efficacy of epidural corticosteroid injections for sciatica. Methods: Three epidural injections (two day intervals) of 2 ml prednisolone acetate (50 mg) or 2 ml isotonic saline were administered to patients with sciatica presumably due to a disk herniation lasting 15–180 days. Self evaluation was the main judgment criterion at day 20. Patients who recovered or showed marked improvement were considered as success. Pain measured by VAS, the SLR test, Schober's test, Dallas pain questionnaire, and the Roland-Morris index were evaluated at days 0, 5, 20, and 35. Only analgesics were authorised, patients requiring non-steroidal anti-inflammatory drugs (NSAIDs) before day 20 were considered as failure. Results: 42 patients were included in the control group (CG), 43 in the steroid group (SG). On an intention to treat analysis 15/42 (36%) in the CG and 22/43 (51%) in the SG (p=0.15) were considered as success (difference 15.5%, 95% CI (−5.4 to 36.3)). Among the 48 failures, 14 patients (6 CG, 8 SG) required NSAIDs, 3 (2 CG, 1 SG) required surgery, and 7 (3 CG, 4 SG) other treatments. On analysis according to protocol, in 74 remaining patients 12/35 (34%) in the CG and 22/39 (56%) in the SG (p=0.057) were considered as success (difference 22.1%, 95% CI (0.0 to 44.2)). For all secondary end points intragroup improvement with time was significant, but intergroup differences were not. Conclusion: The efficacy of isotonic saline administered epidurally for sciatica cannot be excluded, but epidural steroid injections provide no additional improvement.